Analisis Faktor-Faktor Penyebab Perilaku Merokok Remaja di SMK “X” Surakarta - Fathin Faridah (Jurnal Kesehatan Masyarakat (Undip), 2017)
A number of studies from the International Tobacco Control showed that, the implementation of pictorial health warnings have an impact on smoker to quit smoking. In Indonesia, there is Regulation of Health Minister No. 28/2013 about Implementation of Health Warnings and Health Information on Tobacco Product, which regulate the implementaion of pictorial health warnings on tobacco produck.  The purpose of this research is to analyze the factors that causing smoking behavior in adolescents. The population is active students of SMK “X” in Surakarta in grade 10th and 11th,  with a total of 1266 people and as many as 100 samples were taken using a random sampling method with proportional stratified random sampling technique. The whole question has been tested for validity and reliability. Analysis of data using statistical analysis of Chi Square test (significance level 0.05). The results showed that, most of the respondents’ gender is male (95%), most of the respondents were 16-19 years of age (late teens) (81%), and the grade level of the respondents were in grade 10th(52%). The variables associated with adolescents smoking behavior, which are : gender (p= 0.000), the attitude (p = 0.001), exposure to pictorial health warnings on cigarette packs (p= 0.010), support from familiy (p= 0.006), and peer support (p = 0.001). The suggestion on this research are, the government should implement of pictorial health warnings more domineering and more informative both in cigarette packs or mass media.